Effect of geometry on flow structure and pressure drop in pneumatic conveying of solids along horizontal ducts (2011)
This study presents further developments in Euler/Lagrange approach to calculate confined particle-laden flows in pneumatic conveying lines. Special emphasis is placed on influence of particle-wall collisions and wall roughness as well as inter particle collisions with possible agglomeration on developing two-phase flow structure and resulting process parameters. Model sand numerical method were validated based on pressure drop measured along a 6 m horizontal channel, and agreement was found to be excellent for different particles sizes, mass loading and wall roughness. In a horizontal pipe flow, due to wall roughness induced focussing of particle trajectories towards the core of pipe, a secondary flow in pipe cross-section develops. Additional pressure drop due to particles in pipe flow was higher than that in channel due to different wall collision behaviour